2022
DOI: 10.1097/md.0000000000028641
|View full text |Cite
|
Sign up to set email alerts
|

Perception of cosmetic surgery and associated side effects

Abstract: This study explores the perception of female college students in South Korea regarding cosmetic surgery and its side effects. Face-to-face interviews were conducted with 28 female college students over a period of 4 months, starting in October 2019. All participants were female college students who had not undergone cosmetic surgery. The collected data were analyzed qualitatively, using conventional content analysis. Four categories and 13 subcategories were extracted from 112 meaningful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…76 Cosmetic surgery rates in South Korea have grown dramatically over the last decade, mimicking trends in other East Asian countries. 77,78 Studies have found that women gave higher overall ratings than males, indicating that they were more receptive to cosmetic surgery. After adjusting for participant sex, multiple regression analysis revealed that the only significant predictor of cosmetic surgery acceptance was overall body acceptance, indicating that individuals may regard cosmetic surgery as a method for improving their body image.…”
Section: Demographic Patterns and Attitudes Toward Cosmetic Surgerymentioning
confidence: 99%
“…76 Cosmetic surgery rates in South Korea have grown dramatically over the last decade, mimicking trends in other East Asian countries. 77,78 Studies have found that women gave higher overall ratings than males, indicating that they were more receptive to cosmetic surgery. After adjusting for participant sex, multiple regression analysis revealed that the only significant predictor of cosmetic surgery acceptance was overall body acceptance, indicating that individuals may regard cosmetic surgery as a method for improving their body image.…”
Section: Demographic Patterns and Attitudes Toward Cosmetic Surgerymentioning
confidence: 99%